Studi Hasil Belajar Tari Siswa Antara Menggunakan Metode Cooperative Learning Tipe Think-Pair-Share Dengan Metode Konvensional Di SMA 2 Kelas XI IPS Sijunjung - Rara Vidi Ayu; Yuliasma Yuliasma; Afifah Asriati (FBS Universitas Negeri Padang, 2019)
This article aimed to describe the differences and observe the learning outcomes of students in dance subjects using conventional methods with the Cooperative Learning type Think-Pair-Share. The type of this research was experimental research. The population in this reserach were all students of class XI IPS SMA 2 Sijunjung. The method of sampling used random sampling techniques with selected classes based on the same average, namely XI IPS 3 and XI IPS 2. The types of data in this research were primary and secondary data. The research instrument was a test. Data collection techniques were carried out by observation, and tests. The techniques of data analysis were done by the steps of normality test, homogeneity test and hypothesis test. The results of the research showed that there were differences in students’ learning outcomes of dance in class XI IPS 3 (experiment) with the average 84.45 using the cooperative learning method think-pair-share type with the results of learning dance as well as in class XI IPS 2 (control) with an average grade of 80.12 using conventional learning methods. The improvement of students’ learning outcomes in class XI IPS 3 (experiment) and in class XI IPS 2 (control) using cooperative learning methods think-pair-share type with conventional learning methods that were strengthened by testing obtained a significance value of 0,000 (0.003 <0, 05) means that there were significant differences in the students learning outcomes of dance arts using the cooperative learning method think-pair-share type with the students’ learning outcomes of dance arts using conventional learning methods. This was supported by the value of tcount> t table (3.275> 2,0002) with dk= 60 (n1 + n2-2 = 31 + 31-2). Thus, it can be concluded that the proposed hypothesis H0 is accepted and the proposed H1 is rejected.